Road grade estimation for vehicle emissions modeling using electronic atmospheric pressure sensors - Meng, Xiangrui; Pang, Kaili; Di, Baofeng; Li, Wei; Wang, Yongdong; Zhang, Ji; Xu, Yi (Frontiers in Environmental Science, 2023)
Vehicle specific power (VSP) is useful for estimation of vehicle emissions. Previous research has indicated that VSP and emissions are sensitive to variation of road grade. Several methods have been used for acquisition of road grade data in earlier studies, but all have certain limitations such as insufficient accuracy, complicated data processing, or requirements for devices or data that are not easily available. The objective of this study was to develop and verify a road grade measurement framework based on an electronic pressure sensor. The method includes atmospheric pressure acquisition using electronic sensors, determination of the pressure-altitude relationship based on meteorological station data, filtering of altitude data by Fourier transform, and grade calculation combined with the OBD distance. Road grades and VSP calculated based on atmospheric pressure were found reliable and accurate, which also improved the accuracy of vehicle emission rates calculation.